1985
DOI: 10.1029/ja090ia10p09541
|View full text |Cite
|
Sign up to set email alerts
|

The boundary layers as the primary transport regions of the Earth's magnetotail

Abstract: A comprehensive survey of ISEE and IMP LEPEDEA plasma measurements in the earth's magnetotail reveals that the magnetospheric boundary layer and the plasma sheet boundary layer are the primary transport regions there. These plasma measurements also distinguish various components of the plama sheet, including the central plasma sheet and plasma sheet boundary layer. A significant new result reported here is the existence of cold‐and hot‐plasma components that are spatially copresent within the central plasma sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
103
1
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(111 citation statements)
references
References 33 publications
6
103
1
1
Order By: Relevance
“…Kovrazhkin et al (1987) and Zelenyi et al (1990) found within the Polar Diffuse Aurora] Zone specific VDIS-2 events (Velocity-Dispersed Ion Structures of the second type) from lowaltitude AUREOL-3 satellite in about 10% of passes. The VDIS-2 events were shown to be corresponding in width and velocity dispersion direction (energy increase with increasing latitude) to the projected to ionosphere velocity-dispersed ion beams of the Plasma Sheet Boundary Layer (PSBL) as measured in situ from ISEE orbits by Eastman et al (1985), , and Takahashi and Hones (1988). This inference was confirmed by Frank and Craven (1988) who traced a field line from the ISEE location inside the PSBL to the oval poleward boundary with a bright arc.…”
Section: Introduction Some History and Limitationssupporting
confidence: 58%
See 1 more Smart Citation
“…Kovrazhkin et al (1987) and Zelenyi et al (1990) found within the Polar Diffuse Aurora] Zone specific VDIS-2 events (Velocity-Dispersed Ion Structures of the second type) from lowaltitude AUREOL-3 satellite in about 10% of passes. The VDIS-2 events were shown to be corresponding in width and velocity dispersion direction (energy increase with increasing latitude) to the projected to ionosphere velocity-dispersed ion beams of the Plasma Sheet Boundary Layer (PSBL) as measured in situ from ISEE orbits by Eastman et al (1985), , and Takahashi and Hones (1988). This inference was confirmed by Frank and Craven (1988) who traced a field line from the ISEE location inside the PSBL to the oval poleward boundary with a bright arc.…”
Section: Introduction Some History and Limitationssupporting
confidence: 58%
“…The spectacular discoveries of the Plasma Sheet Boundary Layer (PSBL) with high energy ion beams by Williams (1981) and Eastman et al (1984Eastman et al ( , 1985 revived the long sought hope to locate the Distant Neutral Line, DNL, in the tail. Many researches considered the role of the DNL in generation of discrete auroral forms of the oval starting from the pioneering work by Akasofu and Chapman (1961).…”
Section: Introduction Some History and Limitationsmentioning
confidence: 99%
“…These appear to be the same kind of flows that have been equated with a plasma sheet high-latitude ''boundary layer'' in the literature, the PSBL [e.g., Forbes et al, 1981;Eastman et al, 1985;Bosqued et al, 1993;Onsager and Mukai, 1995 and references therein]. The TIMAS observations, which were made at R(SM) $ 4-7 R E, revealed that when the 1-to 33-keV protons are distinctly dispersed in energy within the transition region between the plasma sheet and the (northern) lobe, dispersion has a downward slope as function of time, whether the satellite is moving poleward or equatorward, implying that those proton flows are in fact transient bursts, several of which usually appear in rapid succession over the course of tens of minutes at Polar and are accompanied by hot ($keV) electrons.…”
Section: Present Contextmentioning
confidence: 99%
“…It is the primary region of mass, energy, and momentum transport in the magnetotail during quiet times [Eastman et al, 1985], although during more active periods bursty bulk flow events in the central plasma sheet are thought to dominate [Baumjohann et al, 1990;Angelopoulos et al, 1992Angelopoulos et al, , 1994. Observations of the PSBL from a single spacecraft are often of short duration because of the flapping and kink-like motions of the magnetotail that move it in the ±Z GSE and ±Y GSE directions, respectively [Grigorenko et al, 2007].…”
Section: Introductionmentioning
confidence: 99%